Efektivitas Program Samsat Keliling dalam Pelayanan Wajib Pajak Kendaraan Bermotor di Samsat Padang Pariaman - Ferdana, Reza Fyhalevi; Jumiati, Jumiati (ARZUSIN, 2023)
This research aims to analyze the effectiveness of the mobile samsat program in motor vehicle tax payer services at samsat Padang Pariaman. This research discusses the success of the mobile samsat program in motor vehicle tax payer services at samsat Padang Pariaman seen from aspects of program effectiveness. In this research the author used qualitative research methods through case studies and data collection through interviews, observation and literature study. The results of this research show that the mobile Samsat program for motor vehicle taxpayer services has been operating quite effectively, where the mobile Samsat program which is already operating has had a good influence on the taxpayer community who want to pay motor vehicle tax without having to go to the Samsat office.